THE POWER TO FULFILL THE DESTINY OF ELY REFLECTED IN ALBERT HUGHES’S THE BOOK OF ELY (2010): A PSYCHOSOCIAL ANALYSIS - SANDI, HENRI ARISTYA (2011)

(untitled)
This research is aimed to analyze the structural elements of The Book of Eli movie by Albert Hughes with psychosocial approach. There are two objectives; the first is to analyze the movie in term of structural element and the second is to analyze the movie based on psychosocial perspective. This research is a qualitative research, using the movie of Albert Hughes’s The Book of Ely as the object of analysis of the study. There are two kinds of data sources, primary and secondary. The primary data are the movie and the script of the movie and the secondary data sources are some book, internet and articles related to the subject. The technique of data collecting in this research is by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis The results of study are as follows; first, from the structural analysis, the result illustrates that each of the element are interconnected to each other and form solid unity. The second, based on the psychosocial analysis, the stage of life-span development of Eli is the believe in God, faith and religion. The proof of the Eli’s power on faith appears almost in every activity on his journey such as reading the bible before he sleeps, says part of the verse on the bible before he fights, and still continue his journey even he gets wound from the gun shoot.